Stat3 Activation Is Required for Cellular Transformation by v-src - Bromberg, Jacqueline F. (American Society for Microbiology, 1998)
Stat3 activation has been associated with cytokine-induced proliferation, anti-apoptosis, and transformation. Constitutively activated Stat3 has been found in many human tumors as well as v-abl- and v-src-transformed cell lines. Because of these correlations, we examined directly the relationship of activated Stat3 to cellular transformation and found that wild-type Stat3 enhances the transforming potential of v-src while three dominant negative Stat3 mutants inhibit v-src transformation. Stat3 wild-type or mutant proteins did not affect v-ras transformation. We conclude that Stat3 has a necessary role in v-src transformation.